2015
DOI: 10.1093/geront/gnv080
|View full text |Cite
|
Sign up to set email alerts
|

New Estimates of the Sandwich Generation in the 2013 Panel Study of Income Dynamics

Abstract: These findings are the first to show that both men and women are likely to provide transfers to two generations and that transfers to two generations are common across adult ages. Our findings suggest a need to rethink the notion of the sandwich generation, which has focused on women in late middle age, to include men and women across younger and older ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 17 publications
(21 reference statements)
0
31
1
1
Order By: Relevance
“…Among adults in midlife, these may well include the cumulative and competing demands of employment (Lima, Allen, Goldscheider, & Intrator, 2008;Marks, 1998) as well as those posed by the needs of their children, including those transitioning into adulthood. In recent research, those in midlife (as well as the young-old, particularly women) are often viewed as being "sandwiched" between the simultaneous demands of caring for their aging parents or parents-in-law and their young adult, partially dependent, children (Fingerman, Pillemer, Silverstein, & Suitor, 2012;Friedman, Park, & Wiemers, 2017;Grundy & Henretta, 2006). This occurs as young adult children increasingly delay marriage, parenthood, and careers as well as seek financial and housing support from their parents in response to economic downturns and the greater needs for higher education that shape the recent socioeconomic contexts within which their caregiving takes place (Igarashi, Hooker, Coehlo, & Manoogian, 2013;Mitchell, 2014).…”
Section: Background In Theory and Researchmentioning
confidence: 99%
“…Among adults in midlife, these may well include the cumulative and competing demands of employment (Lima, Allen, Goldscheider, & Intrator, 2008;Marks, 1998) as well as those posed by the needs of their children, including those transitioning into adulthood. In recent research, those in midlife (as well as the young-old, particularly women) are often viewed as being "sandwiched" between the simultaneous demands of caring for their aging parents or parents-in-law and their young adult, partially dependent, children (Fingerman, Pillemer, Silverstein, & Suitor, 2012;Friedman, Park, & Wiemers, 2017;Grundy & Henretta, 2006). This occurs as young adult children increasingly delay marriage, parenthood, and careers as well as seek financial and housing support from their parents in response to economic downturns and the greater needs for higher education that shape the recent socioeconomic contexts within which their caregiving takes place (Igarashi, Hooker, Coehlo, & Manoogian, 2013;Mitchell, 2014).…”
Section: Background In Theory and Researchmentioning
confidence: 99%
“…Increasing survival into older ages allows more individuals to share their mid-life with older generations, who may be in need of support (Wiemers and Bianchi, 2015), whilst postponement of childbirth and delays in transition into independence mean that more individuals in mid-life have continuing commitments to their (adult) children (Stone et al , 2014). Over the past decade, the number of people at risk of simultaneously providing care for children and parents, the so-called ‘sandwich generation’, has grown (Rubin and White-Means, 2009; Friedman et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, these flows seem to be quite common in the region, where middle-aged parents provide financial support to younger generations, especially in achieving housing independence (see e.g., Cirman, 2006). As Železná (2016) suggested, caring responsibilities tend to accumulate rather than compete with one another and therefore could represent a potential risk of overburden for those who have a general tendency to care, and according to some estimates (see Friedman et al, 2015), over 30% of individuals with living parents and adult children provide transfers to two generations.…”
Section: Discussionmentioning
confidence: 99%
“…An additional factor is also the family situation of the caregivers, which can add to the financial and caregiving burden. Friedman, Park, and Weimers (2015) showed that over 30% of individuals with living parents and adult children provide time and financial transfers to both, and that these transfers are relatively stable across adult ages. Also, the income of caregivers is a relevant factor as lower--income caregivers are associated with higher subjective care burdens (Andren & Emstahl, 2007).…”
Section: Literature Review: Family Transfers and Their Determinantsmentioning
confidence: 99%